Pengembangan Kemampuan Berbahasa Melalui Story Reading Pada Kelompok B Di TK Aisyiyah 64surakarta Tahun Ajaran 2014 / 2015 - Pratama, Wenda Arizta Putri; , Aryati Prasetyarini, S.Pd, M.Pd (2015)
This research aims to develop the language skills of children through Story Reading books to children in kindergarten groups Aisyiyah 64 Surakarta Academic Year 2014/2015. Storytelling is one giving a learning experience for kindergarten children to bring stories to children orally presented stories should be interesting, and invite the attention of the child or can not be separated from the goal of education for kindergarten children. The study was conducted using the method of classroom action research with the number of students 16 11 sons and 5 daughters. Data development of language skills through the Story Reading to children daily records collected by field observation and documentation. Data analysis was performed with descriptive interactive is to describe the implementation of Reading Story average yield - average a child's language development with performance indicators at each cycle. Each cycle is done by observation. Prasiklus stage has not reached the target, the first cycle reaches 67.87%, at this stage of the cycle II reached 81.56%. The results showed that stoy Reading can develop language skills of children in Group B in kindergarten Aisyiyah 64 Surakarta Ajaram year 2014/2015.